(untitled) (European Journal of Marketing and Economics, 2023)
The impact of remittance on international trade is often comparable to tariff changes—since exchange rate represents price of tradable goods. The appreciation of real exchange rate brings about increase in relative demand for competing importing tradable goods above domestic tradable goods given demand for non-tradable, since foreign goods are now cheaper in terms of domestic currency and there is high purchasing ability to do so. Resources re-allocation between tradable and non-tradable sector has been significant in Nigeria. Contribution of the agricultural sector to Nigeria’s GDP has shrunk over the years with the attendant threat to food production and loss of employment opportunities. This study investigates the linear relationship between remittances and real effective exchange rate on one hand and the impact of remittances and exchange rate on tradable and non-tradable sector in Nigeria. Employing DOLS regression technique on annual data ranging from 1981 and 2013, The study found that remittances influence performance of tradable agriculture, manufacturing sector and merchandise export sector in line with Dutch disease idea. Also, we found evidence that changes in exchange rate act as a channel of impact of Dutch disease on all sectors.